Classical entanglement in polarization metrology - Toeppel, Falk; Aiello, Andrea; Marquardt, Christoph; Giacobino, Elisabeth; Leuchs, Gerd (New Journal of Physics, 2014)
Quantum approaches relying on entangled photons have been recently proposed to increase the efficiency of optical measurements. We demonstrate here that, surprisingly, the use of classical light with entangled degrees of freedom can also bring outstanding advantages over conventional measurements in polarization metrology. Specifically, we show that radially polarized beams of light allow to perform real-time single-shot Mueller matrix polarimetry. Our results also indicate that quantum optical procedures requiring entanglement without nonlocality can be actually achieved in the classical optics regime. © 2014 IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05
Keywords: applied classical electromagnetism; entanglement and quantum nonlocality; polarization